Increasing Production Productivity at UMKM Kaca Berkah using the OMAX Method - Ramadhanti, Hafidzah; Prasetyawati, Meri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2025)
UMKM Kaca Berkah found a decrease between the monthly target and output, in the measurement period from October 2020 to March 2021 UMKM Kaca Berkah targeted 4 buffet units per day, but in reality only got 2 to 3 units per day and only 1 month was on target. The productivity index in October 2020 was 14.8%, in November 2020 was 33.3%, in December 2020 was 33.3%, in January 2021 was 18.5%, in February 2021 was 7.4% and in March 2021 was 33.3%. It is necessary to find solutions to increase productivity in UMKM Kaca Berkah especially in their production sector. These obstacles are overcome by knowing the level of productivity which is equipped with data on the manpower ratio and machine working hours ratio. Then the data is analyzed and processed with the method that will be used, Objective Matrix Method (OMAX) by weighting to obtain the total productivity, the Fishbone Method to analyze the causes of the problems obtained and the 5W+1H Method to find solutions that will then be suggested to handle problems. After making improvements in April 2021 and May 2021, the productivity index in April reached 100% and in May also reached 100%.